PENGARUH PERCEIVED VALUE DAN VARIETY SEEKING TERHADAP KEPUASAN PENGGUNA KARTU SELULER DI KOTA PURWOKERTO - Nawarini, Alisa Tri (Faculty of Economics and Business Universitas Jenderal Soedirman, 2015)
Customers satifaction is derived from many ways, especially from customerspsychological feelings. This research has the aims to examine the relationship betweencustomers perceived value and variety seeking behavior toward celuler card customerssatisfaction. This research is conducted in Purwokerto city.This research is quantitative research with survey method. Sampling method usedin this research is purposive sampling by taking 100 celuller card user in Purwokertocity. Data analysis method used in this research is multiple regression analysis.The research results show that : 1) perceived value affecting customerssatisfaction, 2)variety seeking affecting customers satisfaction , 3 perceived value andvariety seeking affecting customers satisfaction. The research implication is thatcompanies celuller card provider is need to design their marketing programs to retaintheir customers satisfaction.